ENSURING SUSTAINABLE DEVELOPMENT OF THE NATIONAL TOURISM THROUGH INTERNATIONAL PRACTICES - Nicolae PLATON (Economica, 2018)
The process of re-launching tourism and its consecration as an important socio-economic branch in the Republic of Moldova can only be possible if the decision-makers have a clear and responsible vision regarding this branch, established through well-structured and formulated objectives, being later materialized in the form of development programs. In this article, the author draws the state authorities’ attention to the issues that persist in the tourism industry and emphasizes the need to declare tourism as a priority branch of the national economy, while urging decision-makers to take into account the international experience in managing this branch by ensuring its sustainable development.